2011
DOI: 10.1007/s10482-011-9681-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the Cepheid Xpert vanA/vanB assay for screening of colonization with vancomycin-resistant enterococci during hospital outbreak

Abstract: This study aimed to assess the efficiency of the Cepheid Xpert vanA/vanB test for detecting vancomycin-resistant enterococci (VRE) colonization during a VanA Enterococcus faecium outbreak and to compare the Cepheid Xpert vanA/vanB (Cepheid, Sunnyvale, USA) test to a culture method with chromogenic medium chromID VRE agar (bioMérieux). The Cepheid Xpert vanA/vanB assay showed sensitivity 61.5%, specificity 79.2%, positive predictive value 61.5% and negative predictive value 79.2%. The results obtained in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…These differences may explain the variations in the observed sensitivity, specificity, PPV, and NPV between the two studies. Two additional studies evaluating the performance of the Xpert vanA showed remarkably lower sensitivity by the assay than by culture (11,23). The limited number of specimens tested (Յ50), as well as the use of stool specimens rather than rectal swabs, might explain the suboptimal performance of the Xpert vanA assay in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may explain the variations in the observed sensitivity, specificity, PPV, and NPV between the two studies. Two additional studies evaluating the performance of the Xpert vanA showed remarkably lower sensitivity by the assay than by culture (11,23). The limited number of specimens tested (Յ50), as well as the use of stool specimens rather than rectal swabs, might explain the suboptimal performance of the Xpert vanA assay in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…The Gene Xpert vanA/vanB assay has improved sensitivity compared to direct cultures; therefore, labor-intensive broth-enrichment is not required (10). However, the results of GeneXpert vanA/vanB have a very low PPV and should be confirmed by culture, especially the vanB gene (23). The possible explanations for the false-positive reactions for vanB were lack of specificity of primers/probes of the PCR assay or the presence of van genes in uncultured bacteria (12).…”
Section: Discussionmentioning
confidence: 99%
“…As part of the infection control measures that have to be taken by the hospital, especially during outbreaks, these time-consuming methods have a high economic impact (3). Several studies evaluated PCR-based methods for rapid detection of VRE, including the Cepheid Xpert vanA/vanB assay (4)(5)(6)(7). This assay runs on the Cepheid GeneXpert system, a fully automated processor that combines DNA extraction, real-time PCR amplification, and detection, providing results within an hour.…”
mentioning
confidence: 99%